Removal of copper ions in aqueous solution by using regular Hydrotalcite (MgAlCO3) / Nurdini Noordin - Noordin, Nurdini (Faculty of Applied Sciences, 2008)
The regular hydrotalcite compound was synthesized by co-precipitation method. Characterization of the compound was demonstrated by using X-Ray Diffraction and Fourier Transform InfraRed (FTIR). XRD result demonstrated good crystalline structure with basal spacing (d003) which is 7.9 A0 and interlayer spacing corresponding to the (d006) was found to be 3.9 A0 . FTIR spectroscopy study showed the strong and broad band observed around 3600–3200 cm_1 centered at 3468.39 cm_1 corresponds to the O–H stretching vibration, bending vibration of H2O at 1630 cm_1 , CO3 shows bands around 1382.15 cm_1 and 618.47 cm_1 which corresponds to Mg-O-Al. The removal of heavy metal of copper by regular hydrotalcite compound was investigated at parameters of contact time, initial copper concentration and adsorbent dosage. The optimum adsorption of copper by using synthesized regular hydrotalcite is observed with 3 hours contact time (77.46% adsorption), adsorbent dosage of 0.2g (98.52% adsorption) and initial concentration of 60 ppm (63.72% adsorption).